Incorporation of RG1 epitope concatemers into a self-adjuvanting Flagellin-L2 vaccine broaden durable protection against cutaneous challenge with diverse human papillomavirus genotypes. Issue 37 (5th September 2017) - Kalnin, Kirill; Chivukula, Sudha; Tibbitts, Timothy; Yan, Yanhua; Stegalkina, Svetlana; Shen, Lihua; Cieszynski, Jacqueline; Costa, Victor; Sabharwal, Robert; Anderson, Stephen F.; Christensen, Neil; Jagu, Subhashini; et al.
Highlights: L2 multimer formulated in alum elicits broad immunity against skin challenge lasting >1 year. Multimeric L2-TLR5 agonist fusion elicits immunity over 1 year without exogenous adjuvant. Passive transfer of L2 multimer-specific antiserum conveys broad immunity from skin challenge. Inclusion of the L2 17-38 region in multi-HPV type fusions broadens the spectrum of protection. Protection is mediated by sterilizing immunity. Abstract: Aim: To achieve durable and broad protection against human papillomaviruses by vaccination with multimers of minor capsid antigen L2 using self-adjuvanting fusions with the toll-like receptor-5 (TLR5) ligand bacterial flagellin (Fla) instead of co-formulation with alum. Methods: Fla fusions with L2 protective epitopes comprising residues 11-200, 11-88 and/or 17-38 of a single or multiple HPV types were produced in E. coli and their capacity to activate TLR5 signaling was assessed. Immunogenicity was evaluated serially following administration of 3 intramuscular doses of Fla-L2 multimer without exogenous adjuvant, followed by challenge 1, 3, 6 or 12 months later, and efficacy compared to vaccination with human doses of L1 VLP vaccines (Gardasil and Cervarix) or L2 multimer formulated in alum. Serum antibody responses were assessed by peptide ELISA, in vitro neutralization assays and passive transfer to naïve rabbits in which End-Point Protection Titers (EPPT) were determined using serial dilutions of pooled immune sera collected 1, 3, 6 or 12 months after completing active immunization. Efficacy was assessed by determining wart volume following concurrent challenge at different sites with HPV6/16/18/31/45/58 'quasivirions' containing cottontail rabbit papillomavirus (CRPV) genomes. Results: Vaccination in the absence of exogenous adjuvant with Fla-HPV16 L2 11-200 fusion protein elicited durable protection against HPV16, but limited cross-protection against other HPV types. Peptide mapping data suggested the importance of the 17-38 aa region in conferring immunity. Indeed, addition of L2 residues 17-38 of HPV6/18/31/39/52 to a Fla-HPV16 L2 11-200 or 11-88 elicited broader protection via active or passive immunization, similar to that seen with vaccination with an alum-adjuvanted L2 multimer comprising the aa 11-88 peptides of five or eight genital HPV types. Conclusions: Vaccination with flagellin fused L2 multimers provided lasting (>1 year) immunity without the need for an exogenous adjuvant. Inclusion of the L2 amino acid 17-38 region in such multi-HPV type fusions expanded the spectrum of protection.